Beyond the texts: an archaeological portrait of ancient Israel and Judah - Dever, William G. (Society of Biblical Literature, 2017)
"Cover" -- "Contents" -- "Foreword" -- "Figures" -- "Abbreviations" -- "Chapter 1: âHistory from Thingsâ" -- "Excursus 1.1: A Critique of the European Seminar on Methodology in Israel's History, 1998 - 2010 " -- "Chapter 2: Prelude" -- "Chapter 3: The Emergence of Israel in the Light of History " -- "Excursus 3.1: Raineyâs Transjordanian Shasu as "Earliest Israel" " -- "Excursus 3.2: Finkelsteinâs âSedentarized Pastoralistsâ" -- "Chapter 4: The Rise of Territorial States" -- "Excursus 4.1: C-14 Dates of Megiddo and Tel Rehov " -- "Chapter 5: The Consolidation of the State" -- "Chapter 6: Iron IIC" -- "Conclusion" -- "Works Cited" -- "Biblical Index" -- "Place Name Index